Bimbingan Teknis Karang Taruna Kreatif Kelurahan Sudajaya Hilir - Aziz, Muh. Abdul (PT. Alahyan Publisher Sukabumi, 2023)
Technical guidance for creative cadets is one solution to the problems faced by cadets, namely not being able to recognize their abilities, having business ideas, choosing the right business, and the ability to communicate well. The purpose of this activity is to provide understanding, skills, and motivation to Karang Taruna members in developing their creative potential optimally. The method of implementing this activity is technical guidance to members of the cadet reef of Sudajaya Hilir Village. The partner in this bimtek activity is the Sudajaya Hilir Village Subdistrict. The evaluation was carried out by giving questionnaires to the participants before and after the delivery of the material, and the result was that the comprehension ability of the participants increased by 42.5%.